2018
DOI: 10.1002/ehf2.12363
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health‐related quality of life in heart failure patients attending an outpatient clinic: a pragmatic approach

Abstract: AimsImproving quality of life (QoL) in heart failure patients is a key management objective. Validated health‐related QoL (HR‐QoL) measurement tools have been incorporated into clinical trials but not routinely into daily practice. The aims of this study were to investigate the acceptability and feasibility of implementing validated HR‐QoL instruments into heart failure clinics and to examine the impact of patient characteristics on HR‐QoL.Methods and resultsOne hundred and sixty‐three patients attending heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 24 publications
6
61
1
2
Order By: Relevance
“…Aged 60 and above years had worse mental state, physical health, social relation and environmental health. This nding is lined with previous studies conducted in different research setting (31,32). Based on the knowledge that CHF incidence increases with age, researchers would anticipate that older patients who experience several limitations such as cognitive impairment, loss of personal autonomy, or anxiety and depression may have poor quality of life (31).…”
Section: Discussionsupporting
confidence: 84%
“…Aged 60 and above years had worse mental state, physical health, social relation and environmental health. This nding is lined with previous studies conducted in different research setting (31,32). Based on the knowledge that CHF incidence increases with age, researchers would anticipate that older patients who experience several limitations such as cognitive impairment, loss of personal autonomy, or anxiety and depression may have poor quality of life (31).…”
Section: Discussionsupporting
confidence: 84%
“…Using the cut-off KCCQ-12 of <29, Campbell et al (26) identified 27% of patients with SC needs, while we identified 9%. Compared to our HF patient population, the patient cohort in the Campbell et al study was older and had more co-morbidities, and generally involved a sicker in-patient population (26, 36, 37).…”
Section: Discussionmentioning
confidence: 91%
“…HF patients are often symptomatic and have a poor QoL. 5,25 Improving QoL is acknowledged as a fundamental goal of HF management in the guidelines. 26,27 Heart failure-specific QoL in our study at baseline was moderate (median score 37) and independent of LVEF, which is, for example, comparable with findings in the CHARM programme with a mean MLHFQ summary score of 41.…”
Section: Discussionmentioning
confidence: 99%